HTML5 yu JavaScript Web Apps kai fa shi wu = HTML5 and JavaScript web apps = HTML5 and JavaScript web apps - Hales, Wesley (GoTop Information, Inc., 2013)
Detailed summary in vernacular field.
Includes index
Keywords: HTML (Document markup language); JavaScript (Computer program language); Application software -- Development; HTML (Langage de balisage); JavaScript (Langage de programmation); Logiciels d'application; Développement; HTML; Application software; Development